2012
DOI: 10.1097/ccm.0b013e31823bc9e7
|View full text |Cite
|
Sign up to set email alerts
|

Statins and outcomes in patients with bloodstream infection

Abstract: Background The pleiotropic effects of statins, 3-hydroxy-3 methylglutaryl coenzyme A reductase inhibitor, have been shown to modify inflammatory cell signaling on the immune response to infection. It was postulated that statins may be a good candidate as novel therapeutic agents for the treatment of sepsis. Objective We investigated whether ongoing statin therapy is associated with mortality in patients with bloodstream infection. Design A retrospective cohort study Setting Two tertiary hospitals in Bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
(25 reference statements)
0
20
1
Order By: Relevance
“…In the total cohort of BSI, the unadjusted OR for mortality among statin users compared with non-users did not differ much from what has been found by other investigators [7, 9, 11]. In one study, adjustment for possible confounding factors attenuated the effect measure to a value above 1 [11].…”
Section: Discussionmentioning
confidence: 55%
“…In the total cohort of BSI, the unadjusted OR for mortality among statin users compared with non-users did not differ much from what has been found by other investigators [7, 9, 11]. In one study, adjustment for possible confounding factors attenuated the effect measure to a value above 1 [11].…”
Section: Discussionmentioning
confidence: 55%
“…This statin exposure definition combined both prevalent (of unknown timing and duration) and incident statin users, as well as patients continuing and not continuing statin therapy. Not surprisingly, statin use in this study was not associated with reductions in 90-day mortality, intensive care unit (ICU) admission, or hospital/ICU discharge when adjusting for confounders, including indications for statin therapy, using propensity score methods (17).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, some studies have included patients with such varied statin exposures, and application of the study findings to clinical practice would not be possible. One observational study defined statin use as the presence of a statin on the day of culture regardless of previous or continued use (17). This statin exposure definition combined both prevalent (of unknown timing and duration) and incident statin users, as well as patients continuing and not continuing statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observational studies have shown an apparent decrease in mortality from sepsis associated with the use of statins [72][73][74] but the results are again far from conclusive [75,76]. In a metaanalysis of studies, any benefit from statins observed in retrospective cohorts of patients disappeared when propensity matching and concurrent risk factors were considered [77].…”
Section: 2mentioning
confidence: 96%